Factors influencing the development of speaking skills among Ecuadorian EFL learners: Teachers’ perspectives - Alvarez, Carlos Lenin; Tamayo, Monica P.; Santos, Jardel Coutinho dos (Indonesian Journal of Applied Linguistics, 2024)
Secondary school students in Ecuador face significant challenges in developing English speaking skills, which are crucial for effective communication. This study explores the factors affecting the development of speaking skills and identifies teachers’ suggestions for addressing these challenges. The literature indicates factors on performance, methodology, linguistics, affective, and contextual factors. Employing an explanatory sequential mixed-method design, quantitative data were first collected through a survey of 142 EFL experienced teachers across various Ecuadorian regions, followed by qualitative insights from semi-structured interviews with seven experienced teachers. Findings reveal that large class sizes, limited instructional time, and insufficient speaking-focused activities in course materials impede effective practice. Methodological issues, such as inadequate English exposure outside the classroom, further hinder proficiency. Linguistic challenges include reliance on native language and pronunciation difficulties, while affective factors like anxiety and low confidence also impact students' speaking willingness.  Recommendations include reducing class sizes, increasing instructional time, and including more speaking activities in curricula. These recommendations are not just theoretical but practical and feasible, emphasizing their potential impact on students' oral proficiency. Emphasis is also placed on fostering a supportive classroom environment, enhancing teacher professional development, and integrating authentic language use into lessons. These findings have broader implications for EFL education globally, highlighting the need for curriculum reforms, improved classroom management, and targeted teacher training. The study provides valuable insights into the complexities of teaching and learning speaking skills and offers practical recommendations for enhancing students' oral proficiency.